Fatty acid amides present in Camembert cheese improved cognitive decline after oral administration in mice - Kohei Kawano; Maiko Shobako; Taichi Furukawa; Tatsuhiro Toyooka; Kousaku Ohinata (Neuroscience Research)
Herein, we investigated the effects of Camembert cheese (CC) and its fatty acid contents on cognitive function in mice by employing the object recognition test to evaluate hippocampus-dependent memory. Orally administered CC improved the cognitive decline induced by a high-fat diet. Next, we focused on myristamide (MA), oleamide, and stearamide, which are fatty acid amides produced during the fermentation process of CC. We found that oral administration of MA improved cognitive decline. Notably, an improvement was not observed using myristic acid, a free fatty acid that is not amidated. Thus, fatty acid amidation may contribute to the physiological activity. Moreover, we investigated changes in gene expression related to neurogenesis in the hippocampus. After MA administration, mRNA expression analysis indicated that MA increased hippocampal brain-derived neurotrophic factor expression.